Genetic Defects in the Growth Hormone–IGF-I Axis Causing Growth Hormone Insensitivity and Impaired Linear Growth - Savage, Martin O.; Hwa, Vivian; David, Alessia; Rosenfeld, Ron G.; Metherell, Louise A. (Frontiers in Endocrinology, 2011)
Human genetic defects in the growth hormone (GH) –IGF-I axis affecting the IGF system present with growth failure as their principal clinical feature. This is usually associated with GH insensitivity (GHI) presenting in childhood as severe or mild short stature. Dysmorphic features and metabolic abnormalities may also be present. The field of GHI due to mutations affecting GH action has evolved radidly since the first description of the extreme phenotype related to homozygous GH receptor (GHR) mutations in 1966. A continuum of genetic, phenotypic, and biochemical abnormalities can be defined associated with clinically relevant defects in linear growth. The mechanisms of the GH–IGF-I axis in the regulation of normal human growth is discussed followed by descriptions of mutations in GHR, STAT5B, IGF-I, IGFALS, IGF1R and GH1 defects causing bioinactive GH or anti-GH antibodies. These GH-IGF-I axis defects are associated with a range of clinical, and hormonal characteristics. An up-dated approach to the clinical assessment of the patient with GHI focussing on investigation of the GH–IGF-I axis and relevant molecular studies contributing to the identification of causative genetic defects is also discussed.